Assessment of risk for asthma initiation and cancer and heart disease deaths among patrons and servers due to secondhand smoke exposure in restaurants and bars. Issue 4 (13th February 2013) - Liu, Ruiling; Bohac, David L; Gundel, Lara A; Hewett, Martha J; Apte, Michael G; Hammond, S Katharine
Abstract : Background: Despite efforts to reduce exposure to secondhand smoke (SHS), only 5% of the world's population enjoy smoke-free restaurants and bars. Methods: Lifetime excess risk (LER) of cancer death, ischaemic heart disease (IHD) death and asthma initiation among non-smoking restaurant and bar servers and patrons in Minnesota and the US were estimated using weighted field measurements of SHS constituents in Minnesota, existing data on tobacco use and multiple dose-response models. Results: A continuous approach estimated a LER of lung cancer death (LCD) of 18×10 −6 (95% CI 13 to 23×10 −6 ) for patrons visiting only designated non-smoking sections, 80×10 −6 (95% CI 66 to 95×10 −6 ) for patrons visiting only smoking venues/sections and 802×10 −6 (95% CI 658 to 936×10 −6 ) for servers in smoking-permitted venues. An attributable-risk (exposed/non-exposed) approach estimated a similar LER of LCD, a LER of IHD death about 10 −2 for non-smokers with average SHS exposure from all sources and a LER of asthma initiation about 5% for servers with SHS exposure at work only. These risks correspond to 214 LCDs and 3001 IHD deaths among the general non-smoking population and 1420 new asthma cases among non-smoking servers in the US each year due to SHS exposure in restaurants and bars alone. Conclusions: Health risks for patrons and servers from SHS exposure in restaurants and bars alone are well above the acceptable level. Restaurants and bars should be a priority for governments' effort to create smoke-free environments and should not be exempt from smoking bans.